The Neurological Complications of Nutritional Deficiency following Bariatric Surgery - Danielle A. Becker; Laura J. Balcer; Steven L. Galetta (Hindawi Limited, 2012)
Neurologic complications of bariatric surgery have become increasingly recognized with the rising numbers of procedures and the increasing prevalence of obesity in the US. Deficits are most commonly seen with thiamine, vitamin B12, folate, vitamin D, vitamin E, and copper deficiencies. The neurological findings observed with these nutritional deficiencies are variable and include encephalopathy, optic neuropathy, myelopathy, polyradiculoneuropathy, and polyneuropathy. We review the neurological complications of bariatric surgery and emphasize that these findings may vary based on the specific type of bariatric surgery and time elapsed from the procedure.